Critique of critical thinking. Cartography of contemporary positions regarding critique and some theoretical and clinical orientations on the subject - Karsz, Saul (Critical Proposals in Social Work, 2021)
The article discusses contemporary positions around the notion of critique, questioning both the schemes that comprise it in binary terms -positive acceptation of critique postulated by progressive positions versus negative acceptation of criticism assumed from conservative positions- as well as the neoliberal version of critique. The latter formulates some objections and proposes necessary changes under the essential condition of contributing to the reproduction of the global system. Both the positive and negative meanings of critique are subsumed by this neoliberal version, in which self-proclaimed ‘realist’, ‘constructive’ and ‘modern’ dominate contemporary discourse. The overlaps between these meanings of critique are multiple, going beyond the disciplinary and professional framework in which they are enunciated. In this sense, three theses are proposed on the question of contemporary critique: i) there is no critique in general, indeterminate, without precise orientation, without explicit or implicit social commitment, without theoretical framework or ideological positioning; ii) all critical meanings mobilize subjective logics which are, at the same time, irreducible; and iii) the binomial “necessary objectivity / impossible neutrality” plays a determining role in the different meanings, in their internal dynamics, in their alliances and in their divergences, and also in adhesions and rejections. Finally, a reflection is offered on the safeguards that critical thinking should satisfy in order to continue its task and face, with some success, the challenges of the contemporary moment.